Responsibility of Business Actors to Consumers Harmed by the Use of Skincare Products That Have Their Distribution Licenses Revoked (Case Study Hn-Hetty Nugrahati Skincare Products) - Kezia Br Manalu; Roida Nababan; Besty Habeahan (UNIVERSITAS PAKUAN, 2026)
The circulation of dangerous skincare products whose distribution permits have been revoked, as in the case of HN (Hetty Nugrahati) skincare products, poses a serious threat to public health and demands strict legal accountability from business actors. This study aims to analyze the form of business actors' responsibility towards consumers who experience health losses based on Law Number 17 of 2023 concerning Health, and to examine the role of the Food and Drug Monitoring Agency (BPOM) in supervising cosmetic products that violate technical requirements. The research method used is descriptive juridical with a case study approach. Data analysis was conducted qualitatively descriptive juridical by reviewing relevant primary and secondary legal materials. The results of the study indicate that business actors bear absolute responsibility (strict liability) to provide compensation for health damage suffered by consumers due to the use of products that do not meet safety standards. BPOM plays an important role through pre-market and post-market supervision functions, providing public warnings, and revoking distribution permits to ensure legal certainty. However, coordination in the mechanism for providing consumer compensation is still not optimal. It is recommended that BPOM strengthen the inspection system to prevent administrative negligence and that business actors be more proactive in fulfilling consumers' right to compensation. Key Words : Strict Liability, Consumer Protection, Skincare, BPOM, Distribution Permit.